REASSESSING MEN 1 P.Ala541Thr: NON-DELETERIOUS POLYMORPHISM OR UNDERESTIMATED RISK? - A, Mohd Hazriq; M, Aimi Fadilah; EW, Nur Aini; Z, Aisyah; MS, Fatimah Zaherah; AG, Rohana (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Multiple endocrine neoplasia type 1 (MEN 1) is an autosomal dominant hereditary tumor syndrome caused by inactivating mutations in the MEN 1 tumor suppressor gene. Germline mutations in MEN 1 show high penetrance and account for approximately 70–80% of diagnosed MEN 1 cases. Several polymorphisms have also been identified within the MEN 1 gene region, with at least 12 benign variants reported in the general population. While these variants are typically considered non-pathogenic, the c.1621A>G variant has been reported in some studies as potentially contributing to a low-penetrance MEN 1 phenotype in certain carriers. CASE We report a case of a 56-year-old female who presented with a 3-month history of painless jaundice and anorexia. She had no personal or family history of malignancy or endocrine disorders. Investigations revealed cholestatic jaundice (bilirubin 89 µmol/L), and hypercalcemia (2.88 mmol/L). Imaging showed a solitary 1.7 cm enhancing pancreatic head lesion. Biochemical workup indicated primary hyperparathyroidism (intact-PTH 22.9 pmol/L [normal range; 1.96 – 8.49], calcium/creatinine clearance ratio 0.04). She underwent Whipple’s procedure, and histopathology confirmed a 2.1 cm grade 1 pancreatic neuroendocrine tumor (T2N0). Gallium-68 PET/CT showed no distant disease but identified a right lower thyroid lobe focus, suggestive of a parathyroid adenoma. Pituitary MRI was unremarkable. She met the 2 hallmark features for MEN 1; primary hyperparathyroidism and a pancreatic neuroendocrine tumor, although her presentation occurred later than is typical for MEN 1 cases. The whole exome sequencing showed no pathogenic MEN 1 mutation but detected a c.1621A>G variant that is classified as non-deleterious polymorphism. Interestingly, pathogenic variants in TP53 and BRCA1 were identified without phenotypic expression to date. CONCLUSION This case raises questions about the possible pathogenic role of the MEN 1 c.1621A>G variant, especially considering previous reports linking it to low-penetrance MEN 1. Its coexistence with mutations in TP53 and BRCA1 further suggests potential gene-gene interactions or modifier effects, warranting further investigation.